Hollow cobalt carbide cubes / reduced graphene oxide nanocomposite via cyanide coordination polymer for supercapacitor applications - Aboelazm, Eslam Atef Abdelaziz; Khe, Cheng Seong; Muhammad Fadhlullah, Abd Shukur; Mohamed Saheed, Mohamed Shuaib; Mohammed Ali, Gomaa Abdelgawad; Chong, Kwok Feng (Trans Tech Publications Ltd., 2024)
Coordination polymers, a broad class of porous hybrid materials resulting from the connection of metal ions with organic ligands, showcase enduring porosity, well-organised crystalline structures, and open metal active sites that augment their metal ions' redox activity. This investigation focuses on examining a nanocomposite composed of cobalt carbide/reduced graphene oxide (Co3C/rGO) prepared through the copolymer method, serving as an electrode material for supercapacitor devices. The nanocomposite's structure and hollow cubic morphology were confirmed through X-ray diffraction, Raman spectroscopy, and field emission scanning electron microscopy (FESEM) analysis. Electrochemical properties were thoroughly assessed using cyclic voltammetry, electrochemical impedance spectroscopy, and galvanostatic charge/discharge in 6M KOH with a voltage window of 0 V to 0.5 V. The Co3C/rGO electrode exhibited notable electrochemical performance, displaying a specific capacitance of 486.6 F g-1 at 1 mV s-1 and a low internal resistance of 0.58 Ω, surpassing existing literature due to its porous morphology. Additionally, to evaluate the nanocomposite's cycling stability, 5000 charge/discharge cycles were conducted, revealing a capacitive retention of 82% of its original capacitance after 5000 cycles. This underscores its excellent long-term durability as a high-performance material for supercapacitor applications.